Condensed Osmaquinolines with NIR‐II Absorption Synthesized by Aryl C−H Annulation and Aromatization - Cui, Fei‐Hu; Li, Qian; Gao, Le‐Han; Ruan, Kaidong; Ma, Kexin; Chen, Siyuan; Lu, Zhengyu; Fei, Jiawei; Lin, Yu‐Mei; Xia, Haiping (Angewandte Chemie International Edition, 2022)
The structural design and tuning of properties of metallaaromatics are crucial in materials and energy science. Herein, we describe the rapid synthesis of tetracyclic metallaaromatics containing quinoline and pentalene motifs fused by a metal‐bridged fragment. These unique compounds display remarkably broad absorption, enabling for the first time the absorption of metallaaromatics to reach the second near‐infrared (NIR‐II) bio‐window. The formation of osmaquinoline unit involves an unconventional C(sp2)−C(sp3) coupling promoted by AgBF4 to achieve [3+3] cycloaddition. The introduction of cyclic dπ‐pπ conjugation and extension of the aromatic π‐framework can effectively shrink the HOMO–LUMO gap, thus broadening the absorption window. The considerable photothermal conversion efficiency (PCE) in both the NIR‐I and NIR‐II windows, the high photothermal stability and the excellent electrochemical behavior suggest many potential applications of these condensed metallaquinolines. The synthesis of condensed metallaquinolines capable of NIR‐II absorption involves an unconventional C(sp2)−C(sp3) coupling through the combined effects of Ag and Os. This work demonstrates an unusual reactivity pattern of anthranil and contributes a new approach to N‐doped condensed metallacycles. It also illustrates a new cyclic dπ‐pπ conjugation strategy for the design of NIR‐II absorbing molecules.